The Role of Corporate Social Responsibility and Reputation Management in Global Marketing Success - Suparjo, Suparjo; Dana, Yoga Adhi (Economic and Business Horizon, 2024)
In an increasingly dynamic global economy, companies face significant challenges in ensuring that their marketing strategies are aligned with the principles of ethics, social responsibility, and reputation management. This study examines the importance of ethics in global marketing as a foundation for business success, highlighting how the application of ethical principles can build consumer trust and reduce reputational risk. In addition, corporate social responsibility (CSR) is analyzed as a strategy that can enhance brand image and create long-term value. This study also highlights the crucial role of reputation management in strengthening corporate competitiveness in competitive international markets. Through a literature review and empirical analysis, this study concludes that the integration of ethics, CSR, and reputation strategies is a key factor in determining business sustainability in the global economy. By implementing responsible and transparent business practices, companies can achieve sustainable success and build stronger relationships with consumers and stakeholders.